Odpowiedzi

2009-09-11T07:41:05+02:00
A)
-2,(7) = x /×10
10x = -25 + (-2.7)
10x = - 25 - x
9x = - 25 /÷ 9
x = - 25/9 (ułamek)

11.(3) = x /×10
10x = 113.(3)
10x = 102 + 11.(3)
10x = 102 + x
9x = 102 /÷9
x = 102/9 (ułamek)

-7.(8) = x /×10
10x = - 78.(8)
10x = -71 + (-7.(8))
10x = -71 + x
9x = -71 /÷ 9
x = -71/9 (ułamek)

17.(3) = x /×10
10x = 173.(3)
10x = 156 + 17.(3)
10x = 156 + x
9x = 156 /÷9
x = 156/9 (ułamek)

2.24 = 224/100 (ułamek)

0.1(5) = x /×10
10x = 1.(5)
10x = 1.45 + 0.1(5)
10x = 1.45 + x
9x = 1.45 /÷9
x = 145/900 (ułamek)

13.2(4) = x /×10
10x = 132.(4)
10x = 119.2 + 13.2(4)
10x = 119.2 + x
9x = 119.2 /÷9
x = 1192/90 (ułamek)

1.2(7) = x /×10
10x = 12.(7)
10x = 11.5 + 1.2(7)
10x = 11.5 + x
9x = 11.5 /÷9
x = 115/90 (ułamek)